Central bank Digital Currencies: Key Aspects and Impact on the Financial system - D. M. Sakharov (Финансы: теория и практика, 2021)
This research discusses various issues associated with central bank digital currency that is identified as a new form of money. This paper aims to identify the key prerequisites for the issuance of central bank digital currencies, to discuss the key characteristics of central bank digital currencies and analyze the possible impact of central bank digital currencies on the financial system. The author uses the methods of synthesis, analysis, logical method, comparison, induction, deduction. The research highlights the key principles that should be considered when making decisions on the issuance of central bank digital currency. The paper emphasizes that the issuance of central bank digital currency can be successful if it has competitive advantages over existing forms of fiat money. The research identifies the main characteristics of central bank digital currencies. The paper discusses whether central banks should pay interest on fiat digital currencies. The author notes that the impact of central bank digital currencies on the financial system is expected to vary in different periods of time depending on the phase of the economic cycle and the level of interest rates in the economy. The research shows that central bank digital currency will stimulate the digitalization of the financial system while at the same time it will not create additional risks to financial stability. Introducing central bank digital currency is primarily aimed at promoting the efficient payment system. Further research is needed into mechanisms for the technical implementation of digital currency issuance, taking into account the possible risks associated with introducing fiat digital money.